PEMANFAATAN SEKITAR EKOSISTEM HUTAN MANGROVE OLEH MASYARAKAT KAMPUNG BUKISI DISTRIK YOKARI KABUPATEN JAYAPURA - Tuhumena, Lolita; Wambrauw, Daniel; Wanimbo, Timiron; Warpur, Maklon; Agamawan, Lalu; Tomasila, Leopold Arthur (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Backround: The existence of mangrove forests has an important meaning for human life and also the environment around it. One of the villages that has a mangrove ecosystem Bukisi Village Yokari District. The existence of mangrove forests can provide benefits both ecological and economic so it is interesting to research. The use of mangrove ecosystem areas has not been carried out properly and will experience damage, So that research on the use around mangrove ecosystems needs to be carried out. Method: This research was carried out for 3 months with primary and secondary data collection on July – September 2022. The data analysis used is quantitative descriptive. Resultas : Utilization carried out around the mangrove area of Bukisi Village are as a fishing ground, Crabs and shellfish, Where to find sources of construction materials, sources of energy materials, Tourist attractions, and sacred areas. Conclusion. Then, Efforts to be made in the development of the mangrove area are the development of carbon sequestration, pay attention to socioeconomic issues, p integrated mangrove management and restoration. Keywords: Utilization of Mangrove Ecosystems, Bukisi Village.